Opioid system manipulation during testicular development: results on sperm production and sertoli cells population - doi: 10.4025/actascibiolsci.v33i2.5940 - Cajú, Fernanda Mafra; Queiroz, Gian Carlo D’Angelo; Torres, Sandra Maria; Tenório, Bruno Mendes; Silva Júnior, Valdemiro Amaro (Acta Scientiarum. Biological Sciences, 2011)
The Sertoli cell has fundamental importance to the development and maintenance of spermatogenesis, as well as it has a directly proportional numerical relationship to sperm production. The proliferative period of this cell in rats occurs between 13 days pre-natal and 21 days pos-natal, when is established the final population in adult animals. The Leydig cell can modulate the Sertoli cell proliferation during fetal and neonatal period through β-endorphin. The manipulation of opioidergic system can promote changes in parameters related to development of nervous, endocrine and reproductive systems. By the way, the main purpose of this present work was to compare the effects of the blockade of opioid receptor blocking in Sertoli cells using naltrexone (50 mg kg-1) during fetal and neonatal period in Wistar rats. According to the results, the manipulation of opioidergic system during pre-natal period reduced the total length of seminiferous tubule and Sertoli cell population in adult rats, but sperm production was normal because this cell has had a compensatory response for spermatozoids support capacity.